If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+x+6=3x+x+6
We move all terms to the left:
3x+x+6-(3x+x+6)=0
We add all the numbers together, and all the variables
3x+x-(4x+6)+6=0
We add all the numbers together, and all the variables
4x-(4x+6)+6=0
We get rid of parentheses
4x-4x-6+6=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| -6m²=-150 | | -74+10x=4x+22 | | 3(x-4)=8x-10 | | -0.8x=0.72 | | 60=5k-70 | | −60x+32=32x+60−60x+32=32x+60 | | 3/4x=11/4-x/6 | | 2+1x=1x+16 | | 7a−a=18 | | 5/x+15/2x=5/4 | | 3x+4+6=19 | | 1+7x=7+8x | | 4-1x+16=10 | | -7/2=-4/3w-5/4 | | -7y-8y-2=-13 | | -7p+14=42 | | (2x+5)+120+55=180 | | -3(x-1)+8(x-3)=6x+7-57 | | 3(x+1)+(×-2)=13 | | -75=-25a. | | 1x+3=82 | | 13w+61+27W-23=180 | | 6n-12=2n+4 | | 10x-(2x+9)=-(15-4x) | | 9x-5=23 | | X+12/6=-x-40/20 | | (k+9)/12=-2 | | 12x+49=2x+9 | | 8.5p+2.25=8.5p+1.10 | | (4x-4)(6x-22)=180 | | 2-(x/3)=-2 | | (x+14)(x+13)=15 |